2014
DOI: 10.1161/circheartfailure.114.001127
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ventricular Restoration Using the Parachute Device in Patients With Ischemic Heart Failure

Abstract: Background— Left ventricle remodeling after anterior wall myocardial infarction leads to increased left ventricle volumes, myocardial stress, and ultimately heart failure (HF). Treatment options are limited for these high-risk HF patients. A study was conducted to assess safety and feasibility of a percutaneous ventricular restoration therapy using the Parachute device in subjects with HF because of a cardiac ischemic event. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 18 publications
6
41
0
4
Order By: Relevance
“…Because most therapies which slow or reverse remodeling also favorably affect the natural history of the HFrEF syndrome, 35 substantial ongoing investigative efforts are examining whether various mechanical approaches to reshaping the ventricle may be a useful therapeutic strategy. Approaches include a percutaneously placed device that internally excludes akinetic or dyskinetic territories leading to less mechanical contractile inefficiency, 38 a hybrid interventional and minimally invasive surgical approach that involves placing anchors across scarred myocardium that are then cinched to exclude the scar and recreate a more normal LV shape, 39 and multiple injections of a biopolymer gel meant to reduce wall stress and prevent further remodeling. 40 These and other approaches have shown signs of efficacy in models or very early human trials, which are often unblinded however, by the nature of the intervention.…”
Section: Devices To Address Remodelingmentioning
confidence: 99%
“…Because most therapies which slow or reverse remodeling also favorably affect the natural history of the HFrEF syndrome, 35 substantial ongoing investigative efforts are examining whether various mechanical approaches to reshaping the ventricle may be a useful therapeutic strategy. Approaches include a percutaneously placed device that internally excludes akinetic or dyskinetic territories leading to less mechanical contractile inefficiency, 38 a hybrid interventional and minimally invasive surgical approach that involves placing anchors across scarred myocardium that are then cinched to exclude the scar and recreate a more normal LV shape, 39 and multiple injections of a biopolymer gel meant to reduce wall stress and prevent further remodeling. 40 These and other approaches have shown signs of efficacy in models or very early human trials, which are often unblinded however, by the nature of the intervention.…”
Section: Devices To Address Remodelingmentioning
confidence: 99%
“…Results are summarized in Table 3. [19] The cumulative incidence of HF hospitalization and death was 16.1%, 32.3% and 38.7% at 12, 24 and 36months respectively. The author concluded that PVR device is feasible and safe up to 3 years post implantation.…”
Section: Clinical Studiesmentioning
confidence: 90%
“…Thus out of 50 patients initially screened for PVR, only 8 patients were implanted with parachute device after proper screening with 2D-ECHO and cardiac CT [18] . Costa et al (2014) [19] reported 3 years outcome in 39 patients with ischemic heart failure, NYHA Class II-IV, EF 15-40% and dilated /akinetic anterior wall apex without the need of revascularization. PVR was successfully done in 31 out of 34 patients (success rate 91%).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…This study demonstrated the potential for a percutaneous device to successfully reduce ventricular volumes in patients with adverse ventricular remodeling after acute infarction up to 3 years [ 18 ]. Of course, limited conclusions regarding clinical benefi t to VPD insertion can be drawn from this small, uncontrolled, initial registry.…”
Section: Ventricular Partitioning Device Clinical Outcomes/clinical Tmentioning
confidence: 92%